THE STUDENTS’ MOTIVATION IN LEARNING ENGLISH LANGUAGE AT THE MECHANICAL ENGINEERING DEPARTMENT OF SRIWIJAYA STATE POLYTECHNIC PALEMBANG - Evi Agustina Sari (Politeknik Negeri Sriwijaya, 2013)
One of the important elements in learning English is motivation. Motivation is the incentive, the need, or the desire that the learner feels to learn the second language. High motivation that the students possess will lead them to be successful language learners. This study is aimed to know the student’s motivation especially in the Mechanical Engineering students of Sriwijaya State Polytechnic Palembang in learning language. The data were obtained through a questionnaire. The findings show that the students have a hig level of integrative motivation and a moderate level of instrumental motivation. The students are highly motivated to learn English because they want to achieve maximum proficiency. They think that English is important for travelling abroad. Their instrumental motivation in learning English is to make them knowledgeable, skillful and educated people and enable them to understand English books, movies, pop musuc, etc.